2020
DOI: 10.1111/ppl.13070
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis and phosphorylation sites identification of the 14‐3‐3 gene family and functional characterization of MeGRF3 in cassava

Abstract: The biological functionality of many members of the 14‐3‐3 gene family is regulated via phosphorylation at multiple amino acid residues. The specific phosphorylation‐mediated regulation of these proteins during cassava root tuberization, however, is not well understood. In this study, 15 different 14‐3‐3 genes (designated MeGRF1 – 15) were identified within the cassava genome. Based upon evolutionary conservation and structural analyses, these cassava 14‐3‐3 proteins were grouped into ε and non‐ε clusters. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In the present study, the prediction of the structure and function of cassava 14-3-3 proteins by bioinformatics shows that 16 cassava 14-3-3 proteins are structurally unstable and evolutionarily highly conserved hydrophilic protein families, in which the secondary structure of Me14-3-3 protein isomers is very similar. Compared with both sequences between MeGRF1-15 from Chang et al (2020) and Me14-3-3I-XVI in the present study, we found 13 sequences that showed 100% similarity, while Me14-3-3IV and MeGRF15 displayed 90% similarity, and Me14-3-3XIV and MeGRF8 showed 99% similarity. However, Me14-3-3II did not have any similarity with the MeGRF family (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the present study, the prediction of the structure and function of cassava 14-3-3 proteins by bioinformatics shows that 16 cassava 14-3-3 proteins are structurally unstable and evolutionarily highly conserved hydrophilic protein families, in which the secondary structure of Me14-3-3 protein isomers is very similar. Compared with both sequences between MeGRF1-15 from Chang et al (2020) and Me14-3-3I-XVI in the present study, we found 13 sequences that showed 100% similarity, while Me14-3-3IV and MeGRF15 displayed 90% similarity, and Me14-3-3XIV and MeGRF8 showed 99% similarity. However, Me14-3-3II did not have any similarity with the MeGRF family (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 52%
“…A previous study showed that 15 different 14-3-3 genes (designated MeGRF1-15) were identified within the cassava genome. Based on evolutionary conservation and structural analyses, these cassava 14-3-3 proteins were grouped into the ϵ and non-ϵ clusters ( Chang et al., 2020 ). In the present study, the prediction of the structure and function of cassava 14-3-3 proteins by bioinformatics shows that 16 cassava 14-3-3 proteins are structurally unstable and evolutionarily highly conserved hydrophilic protein families, in which the secondary structure of Me14-3-3 protein isomers is very similar.…”
Section: Discussionmentioning
confidence: 99%
“…G . WebLogo (Crooks et al ., 2004) diagrams showing the amino acids found in positions P1 (residue 27 in omega) and P2 (residue 51 in omega) in 161 isoforms of 14-3-3 from 13 sequenced Eudicot species ( A. thaliana, Glycine max, Nicotiana tabacum, Malus domestica, Solanum lycopersicum, Camellia sinensis, Manihot esculenta, Hevea brasiliensis, Theobroma cacao, Coffea arabica, Populus trichocarpa, Vitis vinifera, Medicago truncatula ) (Mikhaylova et al ., 2021; Jia et al ., 2022; Zhang et al ., 2022; Zuo et al ., 2021; Chang et al ., 2020; Tian et al ., 2015). Note the wide co-occurrence of the Phe (position P1) and Ala (position P2) in non-epsilon groups, suggesting usefulness of a FA criterion for the epsilon/non-epsilon demarcation.…”
Section: Resultsmentioning
confidence: 99%
“…14–3-3 proteins play important roles in plant growth, development, and stress responses. The completion of genome sequencing of model plants and various crops has allowed a large number of 14–3-3 genes to be identified in several plants, including Arabidopsis (15) [ 12 ], tomato (12) [ 30 ], Vitis vinifera (grape) (11) [ 31 ], peanut (14) [ 32 ], mango (16) [ 33 ], soybean (22) [ 34 ], rice (17) [ 25 , 35 ], Hevea brasiliensis (10) [ 36 ], cucumber (10) [ 37 ], Medicago truncatula (10) [ 38 ], apple (18) [ 39 ], and cassava (15) [ 40 ]. The genome sequence of potatoes was released in 2011 (PGSC, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that plant 14–3-3 genes act as signal mediators in hormone signal transduction pathways regulating plant development and tolerance to various abiotic stresses [ 13 , 20 , 23 , 40 , 42 ]. For example, studies on barley Hv14–3-3 have shown that 14–3-3 proteins are induced by ABA and participate in ABA signaling pathways [ 50 ].…”
Section: Discussionmentioning
confidence: 99%